LOGISTICS BUSINESS LAW IN INDONESIA: A SYSTEMATIC LITERATURE REVIEW ON REGULATORY COMPLIANCE AND CONSUMER PROTECTION - Tribowo Rachmat Fauzan; Ajeung Syilva Syara Noor Silmi Sudrajat (Asosiasi Dosen Muda Indonesia, 2026)
The logistics industry in Indonesia has experienced rapid growth, primarily driven by the expansion of e-commerce and the digital economy. However, this development presents significant challenges regarding regulatory compliance and consumer protection. This systematic literature review examines the legal framework governing Indonesian logistics, including Law No. 8 of 1999 on Consumer Protection and Law No. 38 of 2009 on Posts. Findings indicate that while legal standards for liability and safety exist, operational inconsistencies such as delivery delays, damage to goods, and administrative gaps persist. The review highlights the importance of strict liability principles, the integration of tracking technology, and the need for harmonized regulations to enhance service quality and legal certainty in the sector.